Variability and relationships of agronomic traits of spring soft wheat in the conditions of the northern forest-steppe of Western Siberia - V. N. Pakul (Аграрная наука Евро-Северо-Востока, 2022)
The purpose of the research is to study the variability and relationships of agronomic traits of spring soft wheat in the conditions of the northern forest-steppe of Western Siberia and to identify promising sources for use in the breeding process. Studies were carried out in 2018-2021. The objects of the research were 60 samples of spring soft wheat of various origin (Russia, Kazakhstan, Ukraine, China) from the collections of the N. I. Vavilov All-Russian Institute of Plant Genetic Resources and Kemerovo Research Institute of Agriculture. Twenty-one samples of spring soft wheat with the growing period of 80-85 days have been identified. According to productivity the following samples have been selected: PM-83-17 (KP-072, Kemerovo, Russian Federation) - 236.0 g/m2, Lyutescents 5-17 (KP-073, Kemerovo, Russian Federation) - 240.0 g/m2, Omskaya 35 (k-64459, Omsk, Russian Federation) - 246 g/m2, Siberian Alliance (k-65242, Barnaul, Kemerovo, Russian Federation) - 252 g/m2, Lyutescents 105/4 (KP-071, Kemerovo, Russian Federation) - 294 g/m2, Ekada 70 (k-64547, Ulyanovsk, Russian Federation) - 310 g/m2 (OMGAU 90 standard - 173 g/m2). The Ekada 70 sample had he lowest yield variability, 19.8 %. The closest conjugation between the yield and the number of grains in the ear was revealed (r = 0.3702), the mass of 1000 grains (r = 0.3769) (confidence threshold R = 0.3323). The mass of grain per ear is largely determined by the mass of 1000 grains (r = 0.9879. The most valuable for breeding work are samples of Russian origin distinguished by a complex of traits: Siberian Alliance, Lyutescens 105/4, Ekada 70.